Моделирование структуры данных информационной системы выявления ранних признаков нарушения механизмов гомеостаза биологической системы в экстремальных условиях - Порван, Андрей Павлович; Высоцкая, Елена Владимировна; Новикова, Ирина Владимировна; Макайда, Сергей Владимирович (НТУ "ХПІ", 2017)
В статье предложено моделирование структуры данных информационной системы выявления ранних признаков нарушения механизмов гомеостаза биологической системы в экстремальных условиях на примере организма беременной, нарушение механизмов гомеостаза которой может привести как к гибели плода, так и к смерти самой женщины. Полученные результаты могут быть использованы для исследования процессов нарушения гомеостаза как биологических, так и экологических систем. Речь может идти о нарушениях, которые увеличивают риски возникновения различных угроз биобезопасности.

The article suggests modeling the structure of the data of the information system for detecting early signs of the disturbance of the homeostasis mechanisms of the biological system in extreme conditions by the example of automating the registration of pregnant women during the determination of premature births. These may include violations that increase the risks of various threats to biosafety. The developed data structure is openness, modification and modularity of both the database. At the same time, aspects of the results, related to informatics, can be used to develop methods for formalized description of the processes of disturbance of the homeostasis of ecological systems. These may include violations that increase the risks of various threats to biosafety. These results can be used in the development of test Biosystems allowing diagnosing such disorders homeostasis ecological systems.
Modeling of data structure of the information system for detecting early appearance of a violation biological systems’ homeostasis mechanisms under extreme conditions
Keywords: информационная система; база данных; беременность; преждевременные роды; information system; database; pregnancy; premature birth